Telemedicine preferences in pediatric urology following the COVID-19 pandemic: A caregiver survey - Bates, Tara; Spray, Beverly; Canon, Stephen (Frontiers in Urology, 2023)
Purpose: The COVID-19 pandemic dramatically changed the way many patients interacted with their healthcare providers, with many people being forced to use telemedicine. Our study aimed to investigate if this increased usage of telemedicine impacted pediatric patient caregivers' perception of telemedicine for pediatric urology visits. Materials/Methods: A prospective survey was administered to the caregiver of all patients under 18 years old during their in-person(IP) or telemedicine(TM) encounter. The survey included questions regarding accessibility to and opinions toward telemedicine. Results: In total, 239 caregivers were surveyed: 209 IP and 30 TM. Most caregivers in both cohorts reported being more likely to use telemedicine now than before the pandemic: IP(125/209, 59.8%) and TM(23/30, 76.7%). Caregivers also reported that the severity of their child’s condition would impact their likelihood to utilize telemedicine for evaluation (IP 162/209(77.5%) vs. TM 28/30(93.3%) with caregivers in the TM group even more likely to be influenced by this factor (p = 0.045). Most caregivers in both groups reported they would utilize telemedicine within 60 miles from the provider. Over 80% of families from both groups reported having both a laptop and a cellular phone in their home. Conclusions: The COVID-19 pandemic increased caregivers’ likelihood to utilize telemedicine for care of their child’s pediatric urologic disorder. Factors such as severity of illness, distance from the provider, and the context of the evaluation influenced caregiver preferences for utilization of telemedicine. All families surveyed reported having a device at home to perform telemedicine, with laptops and cellular phones being most common.